Políticas públicas culturais cidade de Vitória-ES (1991-2008) - Souza, Julia Duarte de (2009)
This research involves a historical reading of the cultural events that happened in the City of Vitoria between 1991 and 2008, emphasizing the creation of the Rubem Braga Law and the structuring of the FAFI School of Theater and Dance. Analysing the importance of both movements for the development of the City of Vitoria and the Espirito Santo State, the project seeks scientifically documenting these events and their consequences, tied with a vision of the Political History, contextualizing the information in a systematic way and observing the two movements within the vision of a sustainable Cultural Public Policy, a policy which clearly triggered several positive consequences for the capixaba society as the democratization of the access to cultural goods, at the same time that this access remains questionable due to the low participation of society itself in the process.